Stachydrine targeting tumor-associated macrophages inhibit colorectal cancer liver metastasis by regulating the JAK2/STAT3 pathway - Gui, Yang; Xue, Gengchen; Yuan, Yuyi; Wang, Jingbo; Deng, Shuangjiao; Gao, Fei; Tian, Yushi; Zhao, Zhiqiang; Fan, Heng (Frontiers in Pharmacology, 2025)
IntroductionColorectal cancer (CRC) represents the third most prevalent form of cancer worldwide, with liver metastasis representing a significant contributor to mortality. The interaction between tumor-associated macrophages (TAMs) and tumor cells plays a pivotal role in the development of colorectal cancer liver metastases (CRLM) and represents a promising avenue for therapeutic intervention. Stachydrine (STA), a compound derived from the Leonurus heterophyllus plant, has been shown to effectively inhibit tumor growth through a range of mechanisms.MethodsThe study employed imaging and histopathology to evaluate the efficacy of STA monotherapy in preventing CRLM. The inhibition of M2 macrophage polarization by STA was confirmed through the use of flow cytometry and immunofluorescence. Subsequently, a series of assays, including quantitative reverse transcription polymerase chain reaction (qRT-PCR), flow cytometry, scratch, invasion, and tube formation assays, were conducted to confirm STA’s capacity to impede tumor cell migration, invasion, and angiogenesis in vitro. Western blotting and flow cytometry were employed to elucidate the mechanisms through which STA exerts its effects on tumor metastasis.ResultsIn our research, STA has been shown to attenuate liver metastasis in CRC mouse models by inhibiting the polarization of macrophages to the M2 phenotype. This anti-metastatic effect is dependent on the presence of macrophages. In vitro, STA has been found to impede tumor cell migration, invasion, and angiogenesis by preventing TAMs from polarizing to the M2 phenotype via the JAK2/STAT3 signaling pathway. Moreover, the combination of STA with anti-PD-1 therapy has been observed to restore immune infiltration within the tumor microenvironment and inhibit tumor progression.ConclusionThe findings of this study demonstrate that STA exerts an inhibitory effect on colorectal cancer liver metastasis by targeting macrophages and impeding their M2 polarization via the JAK2/STAT3 pathway. Furthermore, the combination of STA with anti-PD-1 therapy has been observed to enhance the effectiveness of immune checkpoint blockade and reduce tumor spread, indicating the potential of STA to improve the efficacy of immunotherapy for liver metastases.